Desktop grid computing - Cérin, Christophe (CRC Press, 2012)
"This book reviews various approaches in desktop grid computing useful for implementing and solving many important sub-problems of middleware design, such as scheduling, data management, security, load balancing, and fault tolerance. With numerous tables and illustrations, the text balances the theory of designing desktop grid middleware and architecture with practical applications and real-world deployment on large scale platforms. Each chapter presents sub-problems, discusses the theoretical and practical issues, details chosen implementation and experiments, and offers references for further reading"--
Includes bibliographical references and index
Keywords: Grid Computing